2020
DOI: 10.1002/anr3.12043
|View full text |Cite
|
Sign up to set email alerts
|

Transient paraplegia due to subarachnoid haemorrhage following spinal anaesthesia

Abstract: Spinal subarachnoid haemorrhage is a rare complication of spinal anaesthesia, especially following atraumatic lumbar puncture and in the absence of coagulopathies. The initial presentation of spinal subarachnoid haemorrhage is variable and paraplegia with full recovery within a few hours is rare. Bleeding can extend into the intracranial subarachnoid space, but there are only a few reports of symptomatic intracranial and spinal subarachnoid haemorrhage after spinal anaesthesia. We report co-existing spinal sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…There is a small number of reports of acute paraplegia secondary to hemorrhage ( 3 , 4 ). It has also been reported that subarachnoid hemorrhage after spinal anesthesia causes paraplegia ( 5 ). The present case report describes the preoperative and postoperative conditions and postoperative recovery of a patient with acute paraplegia following a ruptured aneurysm.…”
Section: Introductionmentioning
confidence: 96%
“…There is a small number of reports of acute paraplegia secondary to hemorrhage ( 3 , 4 ). It has also been reported that subarachnoid hemorrhage after spinal anesthesia causes paraplegia ( 5 ). The present case report describes the preoperative and postoperative conditions and postoperative recovery of a patient with acute paraplegia following a ruptured aneurysm.…”
Section: Introductionmentioning
confidence: 96%
“…A more feared complication of neuraxial anaesthesia is bleeding, particularly in coagulopathic or anticoagulated patients. Olivei et al remind us that even in the absence of altered coagulation, clinically significant bleeding is possible during apparently atraumatic spinal injection [3]. They report a subarachnoid haemorrhage of possible lumbo‐spinal origin, which resulted in a transient flaccid paraplegia that spontaneously and completely resolved within hours.…”
mentioning
confidence: 99%